2013
DOI: 10.1111/jnc.12610
|View full text |Cite
|
Sign up to set email alerts
|

Triheptanoin partially restores levels of tricarboxylic acid cycle intermediates in the mouse pilocarpine model of epilepsy

Abstract: Triheptanoin, the triglyceride of heptanoate, is anticonvulsant in various epilepsy models. It is thought to improve energy metabolism in the epileptic brain by re-filling the tricarboxylic acid (TCA) cycle with C4-intermediates (anaplerosis). Here, we injected mice with [1,2-13 C]glucose 3.5-4 weeks after pilocarpine-induced status epilepticus (SE) fed either a control or triheptanoin diet. Amounts of metabolites and incorporations of 13 C were determined in extracts of cerebral cortices and hippocampal forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 44 publications
(128 reference statements)
3
44
0
Order By: Relevance
“…A recent retrospective chart review study of 20 of these same patients concluded that extension of the TH diet for three years reduced days required in hospital for clinical complications. [29] Recent animal studies with TH report significant benefit for serious complications such as correction of ventricular hypertrophy and pressure overload in rats [30], relief of ischemic stroke [31] and reduced seizures [32]. These observations indicate that an unrecognized energy deficiency exists in broad areas of disease and may also benefit from TH and carnitine therapy in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective chart review study of 20 of these same patients concluded that extension of the TH diet for three years reduced days required in hospital for clinical complications. [29] Recent animal studies with TH report significant benefit for serious complications such as correction of ventricular hypertrophy and pressure overload in rats [30], relief of ischemic stroke [31] and reduced seizures [32]. These observations indicate that an unrecognized energy deficiency exists in broad areas of disease and may also benefit from TH and carnitine therapy in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the pilocarpine rat model of epilepsy, NKA activity has been shown to be reduced in the acute period but substantially increased in the chronic period (Fernandes et al, 1996; Reime Kinjo et al, 2007). In the same model, it has been recently reported that glucose metabolism and the expression of some enzymes involved in energy metabolism are both decreased in the long-term (Araujo et al, 2014; Hadera et al, 2013). No clear-cut relation has been observed between ATP levels and K + -induced epileptiform activity in epileptogenic rat hippocampus (Marichich and Nasello, 1973).…”
Section: The Potassium (K+) Hypothesis: Depolarization Induced By mentioning
confidence: 91%
“…These actions may contribute to anti-seizure effects. In this regard, the anaplerotic substrate triheptanoin has been shown to raise seizure thresholds in mouse seizure models, and to help restore levels of TCA intermediates [58,59]. Further, replenishment of the TCA cycle may counter seizure-induced energy failure and augment inhibitory neurotransmission [60].…”
Section: Tricarboxylic Acid Cycle Effects and Anaplerosismentioning
confidence: 97%